2015
DOI: 10.1021/jacs.5b02218
|View full text |Cite
|
Sign up to set email alerts
|

Rh(I)-Catalyzed Hydroamidation of Olefins via Selective Activation of N–H Bonds in Aliphatic Amines

Abstract: Hydroamidation of olefins constitutes an ideal, atom-efficient method to prepare carboxylic amides from easily available olefins, CO, and amines. So far, aliphatic amines are not suitable for these transformations. Here, we present a ligand- and additive-free Rh(I) catalyst as solution to this problem. Various amides are obtained in good yields and excellent regioselectivities. Notably, chemoselective amidation of aliphatic amines takes place in the presence of aromatic amines and alcohols. Mechanistic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…[7][8] Despite the impressive achievements, carbonylative boroamidation has not yet been developed which will definitely represents an attractive option for the synthetic community. [9][10][11] By boroamidation, powerful amide group and boron group can be effectively installed. Therefore, developing a new strategy on carbonylative boroamidation toward the preparation of ß-boryl amides is highly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] Despite the impressive achievements, carbonylative boroamidation has not yet been developed which will definitely represents an attractive option for the synthetic community. [9][10][11] By boroamidation, powerful amide group and boron group can be effectively installed. Therefore, developing a new strategy on carbonylative boroamidation toward the preparation of ß-boryl amides is highly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic access to the methylene α-keto amide motif is not readily accessible by Pd-catalyzed carbonylative methodology owing to the uncontrollable generation of carbonylated by-products. 24 Finally, we demonstrate the straightforward scalability of the method by processing 10 mmol of bromobenzene to afford 1.8 g of 2a in 72% isolated yield.…”
Section: Aminocarbonylation Of Aryl and Heteroaryl Halidesmentioning
confidence: 88%
“…Dong et al. reported an elegant rhodium‐catalyzed system for the aminocarbonylation of alkenes with aliphatic amines under ligand‐ and additive‐free conditions, affording N ‐alkyl amides in good to high yields with high regioselectivities (Scheme a) . The authors found that the rhodium complexes, such as Rh(I), Rh(III), and Rh(0) precursors afforded high yields with excellent regioselectivities.…”
Section: Synthesis Of Amides From Alkenesmentioning
confidence: 99%